2015
DOI: 10.1038/srep10507
|View full text |Cite
|
Sign up to set email alerts
|

Micro/Nano Gas Sensors: A New Strategy Towards In-Situ Wafer-Level Fabrication of High-Performance Gas Sensing Chips

Abstract: Nano-structured gas sensing materials, in particular nanoparticles, nanotubes, and nanowires, enable high sensitivity at a ppb level for gas sensors. For practical applications, it is highly desirable to be able to manufacture such gas sensors in batch and at low cost. We present here a strategy of in-situ wafer-level fabrication of the high-performance micro/nano gas sensing chips by naturally integrating microhotplatform (MHP) with nanopore array (NPA). By introducing colloidal crystal template, a wafer-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 64 publications
(74 reference statements)
0
32
0
Order By: Relevance
“…Devices made from fresh SbTO solution show higher mobility at a constant level of doping, which indicates that, perhaps, a lower doping level should be desirable to achieve higher on/off current ratio and lower on/off threshold voltage. 33 In general, from our study, it is apparent that aging of the solution affects the TFTs performance, including field-effect mobility, carrier concentration, on/off current ratio and threshold voltage, more significantly than small fluctuations in the thermal annealing temperature, or local fluctuations in the SbTO properties across each film.…”
Section: Resultsmentioning
confidence: 69%
“…Devices made from fresh SbTO solution show higher mobility at a constant level of doping, which indicates that, perhaps, a lower doping level should be desirable to achieve higher on/off current ratio and lower on/off threshold voltage. 33 In general, from our study, it is apparent that aging of the solution affects the TFTs performance, including field-effect mobility, carrier concentration, on/off current ratio and threshold voltage, more significantly than small fluctuations in the thermal annealing temperature, or local fluctuations in the SbTO properties across each film.…”
Section: Resultsmentioning
confidence: 69%
“…Carbon dioxide (CO 2 ) sensors play an important role in monitoring and controlling indoor air quality. Sensing of CO 2 using inexpensive, miniaturized, highly sensitive sensors that work at room temperature is of great interest for environmental, agricultural applications, Martian atmosphere, and consumer applications 1 . Considering the tremendous impact of CO 2 emissions on the global warming, monitoring of CO 2 has a vital importance in the field of gas sensors.…”
mentioning
confidence: 99%
“…Considering the tremendous impact of CO 2 emissions on the global warming, monitoring of CO 2 has a vital importance in the field of gas sensors. CO 2 sensors are also critical in the food processing industry to maintaining the freshness and shelf life of food, breath analyzers in healthcare, environmental incubators in biotechnology and petrochemical plants in the industry 1 . Also, there is a highly significant need for CO 2 sensors for space and commercial applications including low-false-alarm fire detection inside the spacecraft which detects chemical species indicative of a fire (CO 2 and CO).…”
mentioning
confidence: 99%
“…It has been widely reported that researchers can improve the performance of gas sensors by constantly optimizing the micro-hotplatform (MHP) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) structure and the morphology of sensing materials. (15)(16)(17)(18)(19) For example, in earlier research on MEMS gas sensors, Lee et al (4) described the great advantage of low power consumption compared with traditional gas sensors. Behera and Chandra reported that the heating resistor formed on a SiO 2 platform of 6 μm thickness can save 43.5% of power through planar MEMS technology.…”
Section: Introductionmentioning
confidence: 99%
“…Kadir et al (15) presented well-aligned SnO 2 nanofiber materials that could be operated at 150 ℃ for sensing hydrogen gas. The nanopore array was integrated with the MHP by Xu et al, (16) leading to a strategy of in-site wafer-level fabrication of highperformance and low-power gas sensors. Tan et al reported that an ultrathin nanosheet material mode realized by assembling hollow and hollowed-out Co 3 O 4 microspheres exhibited a high response to ethanol.…”
Section: Introductionmentioning
confidence: 99%